WABP Primary Social Studies Pupils' Book 3 - Odedokun, M O et al (West African Book Publishers Limited, 1994)
This book is a a six book series,one book per year written to the specifics of the new revised National Curriculum on the Subject.
Keywords: Education-Social Studies